Application of Warm Compress Therapy to Reduce Pain in Cholelithasis Patients with Acute Kidney Injury and Liver Insufficiency A Case Study - Putri, Dina Mala; Purba, Chandra Isabella Hostanida; Platini, Hesti (Journal of Nursing Care, 2025)
Cholelithiasis occurs due to the formation of stones in the gallbladder that block the flow of bile, causing right upper abdominal pain, nausea, vomiting, and fever. This case study adds new data that warm compress therapy is effective in significantly reducing pain levels in cholelithiasis patients with complications of acute kidney injury and liver insufficiency aged 59 years. The method used in this study was the Numerical Pain Rating Scale (NPRS) to assess the level of pain, and observation, interview, physical examination, and hospital medical records were used. The NPRS rating scale is a scale of 0 to 10. The number 0 means no pain while the number 10 indicates maximum pain. The application of warm compress therapy was carried out by placing a cloth soaked in 38°C water on the patient's right upper abdominal area, with a duration of implementation of around 15 to 20 minutes for 4 days. The results showed a significant decrease in pain levels after warm compress therapy. Before the intervention, the pain felt was 7/10, and after the intervention, the pain decreased by 4/10 on the fourth day of the intervention. The role of nurses in non-pharmacological pain management, particularly warm compress therapy, includes roles as nursing care providers, educators, and patient safety advocates. However, this study has limitations in the use of cloth as a compressed medium because the cloth is not able to maintain a stable hot temperature during the intervention. As a result, the temperature received by the patient's body may differ from the initial temperature of the compress. Thus, it is recommended that further researchers use special bags, such as hot water bags, for warm compress therapy so that the hot temperature can be maintained more stably and effectively.